Evaluation of two internal fixation techniques for mandibular parasymphyseal fractures comparing conventional titanium miniplates with customised titanium CRB omega miniplates: a prospective study. Issue 6 (July 2018) - Bande, C.R.; Kurawar, K.R.; Mishra, A.; Joshi, A.; Goel, M.; Mahajan, M.R.
Abstract: Our aim was to compare the efficacy and outcome of customised, titanium, CRB (Chandrashekhar Rushiji Bande), omega miniplates with those of conventional titanium miniplates in the management of parasymphyseal fractures of the mandible, with or without involvement of the mental nerve, after clinical and radiographic evaluation. A total of 252 parasymphyseal fractures in 200 patients were selected for the study over the period of seven years (January 2010–January2017) and divided randomly into two groups. The first group included 126 fractures treated with two conventional titanium miniplates (conventional group) and the second 126 fractures treated with one customised, titanium, CRB, omega miniplate (customised group). All operations were done by the same surgeon. Duration of operation (from placement of incision to closure of the defect) was recorded. Postoperative paraesthesia, infection, and acceptability of the plate to patients were also recorded. Postoperative healing was evaluated radiologically at one week and six months postoperatively. Operations were significantly shorter, and significantly fewer patients developed paraesthesia or infection, in the customised group. These patients were also happier with their miniplates, and had good radiological bony healing. In conclusion, a single customised, titanium, CRB, omega miniplate is an effective and economical alternative to two conventional titanium miniplates in the management of parasymphysis fractures of the mandible.